2017
DOI: 10.1002/ece3.3694
|View full text |Cite
|
Sign up to set email alerts
|

Detecting rare carnivores using scats: Implications for monitoring a fox incursion into Tasmania

Abstract: The ability to detect the incursion of an invasive species or destroy the last individuals during an eradication program are some of the most difficult aspects of invasive species management. The presence of foxes in Tasmania is a contentious issue with recent structured monitoring efforts, involving collection of carnivore scats and testing for fox DNA, failing to detect any evidence of foxes. Understanding the likelihood that monitoring efforts would detect fox presence, given at least one is present, is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Similarly, van Hespen, Hauser, Benshemesh, Rumpff, and Lahoz‐Monfort (2019) demonstrated through simulation modelling that small changes in environmental factors, budget constraints and monitoring design can affect the chances of a monitoring programme successfully achieving its intended outcomes. These are crucial considerations for developing effective monitoring programmes, yet there are relatively few examples in the published peer‐reviewed literature where power analysis has been used to inform carnivore monitoring (but see Ramsey et al., 2017; Travaini et al., 2010; van Hespen et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, van Hespen, Hauser, Benshemesh, Rumpff, and Lahoz‐Monfort (2019) demonstrated through simulation modelling that small changes in environmental factors, budget constraints and monitoring design can affect the chances of a monitoring programme successfully achieving its intended outcomes. These are crucial considerations for developing effective monitoring programmes, yet there are relatively few examples in the published peer‐reviewed literature where power analysis has been used to inform carnivore monitoring (but see Ramsey et al., 2017; Travaini et al., 2010; van Hespen et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, wild individuals are harder to source and their removal may compromise established wild populations, especially for threatened species (Todd et al, 2002). Wild quolls from Tasmania are not expected to have an appropriate predator response to foxes on the mainland (Jones et al, 2004); this is due to foxes being absent or occurring at very low densities in Tasmania (Ramsey et al, 2018) and a lack of co‐evolution of the two species (Woinarski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Scats have been used in a number of well-known and universal methodologies for a variety of species and with various specific non-invasive monitoring objectives (Foran et al 1997;Delahay et al 2001;Baines et al 2013;Ramsey et al 2017). In our study, detection dogs successfully found and indicated golden jackal scats with an accuracy of 73%.…”
Section: Discussionmentioning
confidence: 54%
“…In contrast, we assume that humans are not able to distinguish reliably between golden jackal scats and those from closely related canid species, especially in areas of coexistence with the red fox (Vulpes vulpes), a species widespread all over Europe. Moreover, humans have a much smaller overall detection success than dogs (Böcker 2016;Ramsey et al 2017;Grimm-Seyfarth et al 2019).…”
Section: Communicated By: Rafał Kowalczykmentioning
confidence: 99%